2013
DOI: 10.4049/jimmunol.1300083
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of T Cell Ig Mucin-3 Signaling on Central Nervous System Autoimmune Disease Is Determined by the Effector Function of the Pathogenic T Cells

Abstract: Multiple sclerosis (MS) is an inflammatory, demyelinating disease of the central nervous system (CNS) mediated by self-reactive, myelin-specific T cells. Both CD4+ and CD8+ T cells play important roles in the pathogenesis of MS. MS is studied using experimental autoimmune encephalomyelitis (EAE), an animal model mediated by myelin-specific T cells. Tim-3 is a cell-surface receptor expressed on CD4+ IFN-γ-secreting Th1 cells, and triggering Tim-3 signaling ameliorated EAE by inducing death in pathogenic Th1 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 46 publications
(82 reference statements)
1
43
0
Order By: Relevance
“…Astrocytes were sorted from GFAP-GFP transgenic mice as CD45 − GFP + cells and endothelial cells were sorted based on CD31 expression. Microglia and the subset of cells containing macrophages, monocyte and dendritic cells were sorted based on expression of CD45 and CD11b as previously described (14). cDNA was generated using a Power SYBR® Green Cells-to-CT™ Kit (life technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Astrocytes were sorted from GFAP-GFP transgenic mice as CD45 − GFP + cells and endothelial cells were sorted based on CD31 expression. Microglia and the subset of cells containing macrophages, monocyte and dendritic cells were sorted based on expression of CD45 and CD11b as previously described (14). cDNA was generated using a Power SYBR® Green Cells-to-CT™ Kit (life technologies).…”
Section: Methodsmentioning
confidence: 99%
“…These results are consistent with the idea that injection of anti-Tim-3 antibodies disrupts a pathway that restrains Th1-dependent responses. Of note, Lee et al [47] reported that Tim-3 KO mice subjected EAE challenge did not show the same dramatic effects on disease caused by injecting Tim-3 antibodies, although changes were observed that suggest Tim-3 suppresses EAE and Th1-driven responses.…”
Section: Regulation Of Cd4 T Cell Responses By Tim-3mentioning
confidence: 99%
“…Tim-3 was demonstrated to be constitutively expressed on microglia in both mice and humans [7,19]. We verified its expression on the cultured primary microglia by flow cytometry and immunocytochemistry analysis that showed 90.6 ± 4.4% and 93.2 ± 2.4% of microglial cells respectively were positive for the Tim-3 antigen (Fig.…”
Section: Expression Of Tim-3 On Microglia In Vitromentioning
confidence: 72%
“…In addition, consistent with other studies showing Tim-3 participates in the clearance of apoptotic cells [30,31], we demonstrated that Tim-3 is involved in the microglial phagocytosis of apoptotic neurons. A recent study reported that ablation of Tim-3 on microglia does not significantly influence the disease onset, or severity of EAE during a 6-day period of observation [19]. One explanation for this could be that Tim-3 on The signaling pathways underlying Tim-3 regulation of cell function and cell fate remain elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation